ZnO Nanosheets: Precursor‐Directed Self‐Assembly of Porous ZnO Nanosheets as High‐Performance Surface‐Enhanced Raman Scattering Substrate (Small 1/2014). Issue 1 (15th January 2014) - Liu, Qian; Jiang, Li; Guo, Lin
<x xml:space="preserve">Abstract</x> Parallelogram‐shaped porous ZnO nanosheets with high specific surface area are prepared thorough a precursordirected self‐assembly route. The precursor, basic zinc salt, plays dual roles in the assembly that concurrently provides the building blocks and the template. As reported by L. Guo and co‐workers on page 48, this porous ZnO structure with active surface defects serves as a highperformance semiconductor substrate for surface‐enhanced Raman scattering. This assembly strategy delivers a new idea for designing hierarchical structures and a platform for in‐depth investigation of electrochemical properties at the molecule/surface interface. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>